Policy Implementation of Government Regulation No. 7 of 2021 on the Ease and Protection of Small Businesses during the Covid-19 Pandemic in Sonder District - Evi Elvira Masengi,; Elvis M. C. Lumingkewas,; Bella F. Lumenta, (Technium Social Sciences Journal, 2023)
Researchers use qualitative research in this thesis. the purpose of the research to be conducted is to analyze and describe the Policy Implementation of Government Regulation No. 7 of 2021 Concerning the Convenience and Protection of Small Businesses During the Covid-19 Pandemic in Sonder District. The data collection technique that researchers use is starting from the process of entering the research location, and conducting interviews and documentation. Based on the results of the research that has been analyzed and discussed in the previous chapter, a number of conclusions have been drawn in this study, namely related to convenience, the community has not fully felt that the disbursement of these funds has been facilitated, there is no definite schedule for business actors to obtain assistance in the form of capital. Regarding protection, the government, in this case the Civil Service Police Unit, still frequently inspects business premises because they are considered to be causing crowds.